MATHEMATICS LEARNING PROFILE OF JUNIOR HIGH SCHOOL - Pardimin; Rochmiyati, Siti; Wijayanto, Zainnur (PEOPLE: International Journal of Social Sciences, 2020)
The driving factors of the success of mathematics learning activities include models, media and learning resources. However they need to be modified of adjusted in order to facilitate the students to have the ability of reasoning, problem solving, mathematical communication, mathematical connections, mathematical literacy, and mathematical representation. A number of obstacles experienced by teachers and students in mathematics learning activities indicate that it has not been quite successful, as notably occurred in mathematics learning activities in junior high schools in Special Region of Yogyakarta (DIY). Departed from the problems, this study aims to analyze the mathematics learning profile of the junior high schools in DIY, as well as finding solutions to the obstacles faced in learning mathematics which were then developed into good mathematics learning model in accordance with the latest development of science and technology.